SISTEMAS DE PRODUCCION Y CAMBIOS EN LA FERTILIDAD DEL SUELO EN LA RESERVA NATURAL INTEGRAL "LA M.. - Amat García, Germán; Departamento de Biología, Facultad de Ciencias, Pontificia Universidad Javeriana, Bogotá (2013)
At the natural reseiVe "La Macarena'; around river Güejar sector, it was evaluated the production sys.tems of ahifting cultivation in the non - tlooded sites. It was studied the soil making a comparative chemical analysis of the different fallow state, undisturberd forest, crops and chemical contribution of ashes. Palabras clave: Agricultura migratoria -Agricultura itinerante - Rozatum